KIR genotypic diversity in Portuguese and analysis of KIR gene allocation after allogeneic hematopoietic stem cell transplantation. (13th April 2016) - Ligeiro, D.; Buhler, S.; Abecasis, M.; Abade, O.; Sanchez‐Mazas, A.; da Silva, M. Gomes; Trindade, H.
Abstract: The diversity of killer‐cell immunoglobulin‐like receptors (KIR) genes was evaluated in Portuguese and the observed genotypic profiles were found related to the ones reported in European populations. The KIR repertoire after hematopoietic stem cell transplantation is determined by these gene frequencies and the KIR group B motifs are the less common. We estimated donor–KIR/recipient–ligand interactions in transplants with related donors and unrelated donors found in a local registry or from abroad. A large fraction of transplants had all three ligands of inhibitory receptors, and therefore, in theory were not prone to natural killer cell (NK) mediated alloreactivity. Furthermore, the distribution of KIR alloreactive interactions was found independent of the donor–recipient genetic proximity, probably because of different gene segregation and comparable KIR frequencies in the donor pools.